INTEGRATION OF ISLAMIC AND CONVENTIONAL STOCK INDICES BEFORE, DURING, AND AFTER COVID OUTBREAK: EMPIRICAL INSIGHTS FROM FIVE ASEAN COUNTRIES AND THE US - Utami, Alia Tri; Setiawan, Ilham; Annisa, Novita Nur; Muniroh, Rezqya Aulia Azyuranie; Sari, Devi Anita (Finansha: Journal of Sharia Financial Management, 2025)
This study aims to examine the long-term integration among Islamic capital markets in five ASEAN countries namely Indonesia (ISSI), Malaysia (FTSE-MB), Thailand (FTSE-SET), Singapore (FTSE-SGX), and the Philippines (MSCI-PH) along with the U.S. stock market (DJIA) before, during, and after the COVID outbreak. Utilizing a quantitative approach, the study analyzed daily closing prices from November 2018 (a year before the COVID-19 outbreak) to May 2024 (a year following the COVID-19 outbreak). We employed the Johansen cointegration test and the Vector Error Correction Model (VECM) to assess market cointegration. Results reveal that all ASEAN Islamic indices exhibit significant cointegration with the Dow Jones Industrial Average (DJIA). The FTSE-SET and MSCI-PH indices show a strong positive correlation with the DJIA; in contrast, the ISSI and FTSE-SGX indices display a negative correlation, suggesting potential diversification benefits for investors. The Granger Causality Test further identifies causal linkages between certain ASEAN indices and the DJIA. These findings underscore the influence of global dynamics on ASEAN Islamic markets, despite their unique characteristics. The results advocate for portfolio diversification and the formulation of adaptive economic policies to enhance the stability of ASEAN Islamic markets amid global financial volatility.